2022
DOI: 10.1002/vetr.2178
|View full text |Cite
|
Sign up to set email alerts
|

Dutch veterinary graduates leaving practice: A mixed‐methods analysis of frequency and underlying reasons

Abstract: Background This study aimed to evaluate the frequency of veterinarians graduated between 2009 and 2019 in the Netherlands leaving practice, their reasons for leaving and the relative importance of these reasons. Methods Study 1 (focus group sessions, n = 14) of this project was aimed at defining the reasons Dutch veterinarians have for leaving veterinary practice within 10 years of graduation. In study 2, the frequency of veterinarians leaving veterinary practice and the relative importance of the reasons for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…This research revealed a high turnover rate within the veterinary profession-almost one-sixth of graduates left the profession within 3.5 years-with multiple factors influencing individual decisions. 12 The authors highlighted how the JD-R model can be used to understand and explain employee wellbeing (including burnout, job satisfaction and performance) and how these factors may influence individuals' intention to leave the profession, supporting previous research linking exhaustion with increased job demands and insufficient resources among veterinary professionals. 14 However, while identifying common reasons for leaving practice may aid retention, it is unlikely that modifying a single factor will be sufficient; instead, a multifactorial individualised approach is required to reduce turnover.…”
Section: Staff Turnoversupporting
confidence: 59%
See 2 more Smart Citations
“…This research revealed a high turnover rate within the veterinary profession-almost one-sixth of graduates left the profession within 3.5 years-with multiple factors influencing individual decisions. 12 The authors highlighted how the JD-R model can be used to understand and explain employee wellbeing (including burnout, job satisfaction and performance) and how these factors may influence individuals' intention to leave the profession, supporting previous research linking exhaustion with increased job demands and insufficient resources among veterinary professionals. 14 However, while identifying common reasons for leaving practice may aid retention, it is unlikely that modifying a single factor will be sufficient; instead, a multifactorial individualised approach is required to reduce turnover.…”
Section: Staff Turnoversupporting
confidence: 59%
“…However, when considering the free‐text comments, not all respondents intending to remain in the profession had positive opinions; some ( n = 23) highlighted a wish to leave the profession but felt limited by personal circumstances such as a lack of transferrable skills or other qualifications. As highlighted in previous studies, 11,12 numerous factors influence intentions to leave the profession. In this study, increased NFR score was significantly correlated with increased intention to leave the profession but it was not the sole influential factor.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, despite the hugely positive aspects of working in the various sectors of the veterinary profession, veterinary mental wellbeing (MWB) concerns have been linked to the challenging socio-economic and cultural working environment. Over the past decade, numerous reports have identified important stressors for veterinary professionals, such as long working hours [ 2 , 3 , 4 , 5 ], a lower income compared to other medical professionals [ 6 ], insufficient development opportunities, a lack of mentorship [ 7 ], challenging client communications [ 3 , 6 , 8 , 9 , 10 , 11 ], a demanding work–life balance [ 1 , 6 ], and high student debt [ 12 , 13 ], resulting in compassion fatigue [ 14 , 15 ], burnout [ 14 , 15 , 16 , 17 ], veterinarians feeling that they have a life not worth living [ 18 ], moral dilemmas, and other forms of stress [ 19 ]. In particular, early-career female practitioners generally seem to experience more negative stressors compared to more experienced male colleagues [ 2 , 12 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8]14 Whether there is a causal relation is unclear; one study reported that nearly 17% of recent (or new) graduates left private practice within 5 years of graduation. 15 Another study reported that around 23% of older veterinarians opted for early retirement. 16 Given previous studies, [4][5][6][7][8][9]12 we formulated a number of questions concerning the Dutch DS that have been in place since 1993.…”
Section: Introductionmentioning
confidence: 99%